Pembinaan Masyarakat dalam Pemanfaatan Limbah Pertanian Berupa Jerami Padi (Oryza Sativa) Menjadi Bahan Pakan Ternak Fermentasi - Hapsoh, Hapsoh; Wawan, Wawan; Dini, Isna Rahma; Mustika, Syuri (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
Rice straw is rice plant waste which is usually used as animal feed. However, rice straw has a very low nutritional content if used directly when fresh. Therefore, increasing the nutrition of straw as animal feed can be done by fermenting straw. The nutritional difference between fermented and unfermented rice straw is an increase in protein content of up to 15%. This service aims to provide assistance to farmers in Langsat Permai Village in making fermented animal feed made from rice straw. Fermentation activities were carried out using bioactivators and carried out for one month. The service partners are the Rukun Sentosa farmer group which consists of 14 cattle breeders. The results of the activity show that cattle breeders have not optimally processed forage into feed. Farmers use fresh feed more than fermented feed. By providing fermented animal feed production, this can provide another option in providing animal feed. Apart from that, it is hoped that the presence of straw waste can not only be used as compost, but can also be used as fermented animal feed which can overcome the problem of feed availability in the dry season and provide additional nutrition to livestock.